$3x^{2}$ – $\frac{3}{2}$ + 6xy – $8x^{2}$ + $y^{2}$ – $\frac{-5}{3}$xy Thu gọn đa thức

Question

$3x^{2}$ – $\frac{3}{2}$ + 6xy – $8x^{2}$ + $y^{2}$ – $\frac{-5}{3}$xy
Thu gọn đa thức

in progress 0
Jade 4 tháng 2021-08-02T12:01:21+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-08-02T12:02:57+00:00

    `3x^2 – 3/2 + 6xy – 8x^2 + y^2 – (-5)/(3)xy`

    `= 3x^2 – 8x^2 + 6xy – (-5)/(3)xy+ y^2 – 3/2`

    `=-5x^2 + 23/3 xy + y^2 – 3/2`

     

    0
    2021-08-02T12:03:02+00:00

    Đáp án:

    `3x^2-3/2+6xy-8x^2+y^2-(-5)/3xy=-5x^2+23/3xy-3/2+y^2`

    Giải thích các bước giải:

    `3x^2-3/2+6xy-8x^2+y^2-(-5)/3xy`
    `=(3x^2-8x^2)+(6xy-(-5)/3xy)-3/2+y^2`
    `=-5x^2+(6xy+5/3xy)-3/2+y^2`
    `=-5x^2+23/3xy-3/2+y^2`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )